Atherosclerosis in Juvenile Idiopathic Arthritis - Ewa Jednacz; Lidia Rutkowska-Sak (Mediators of Inflammation)
Atherosclerosis is a chronic inflammatory disease of the arteries. Clinical consequences of the atherosclerotic process occur in the adult population, however atherosclerotic process begins in childhood. The classic risk factors for atherosclerosis include obesity, dyslipidaemia, age, gender or family history. In recent years, attention has been drawn to the similarity between atherosclerotic inflammatory processes and inflammatory changes in the course of systemic connective tissue disease, in particular systemic lupus etythematosus (SLE) or rheumatoid arthritis (RA). There is also observed the similarity of the pathogenetic background of development of atherosclerosis and juvenile idiopathic arthritis (JIA). Elevated levels of pro-inflammatory cytokines are observed in the course of juvenile idiopathic arthritis. Also homocysteine concentrations, which may play a significant role in the development of atherosclerotic lesions, are observed higher in patients with JIA. Some studies revealed higher carotid intima-media thickness (IMT) index values in children with JIA. In view of the fact that atherosclerotic process begins as early as in childhood, the introduction of appropriate preventive measures in children is a matter of utmost importance.